(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objectives: The study objectives to detect the effect of angioplasty upon lung functions among Patients with ischemic heart disease and to find out the relationship between the patients lung functions and their demographic and clinical characteristics. Methodology: A descriptive (correlation) design was conducted on the at Al- Najaf center for cardiac surgery and catheterization. Starting from 1st April 2019 to 1st October 2019. In order to detect the effect of angioplasty on lung function among of patient with ischemic heart disease. A non-probability (purposive) sample of (52) patients, those who admitted to angioplasty unit and coronary care unit without any respiratory diseases. Patients were ischemic heart disease. The patients’ demographic and clinical data collected through the utilization the semi-structured questionnaire and by means of interview technique with the subject, while the pulmonary functions test collected by using spirometer instrument. Data was analyzed by using descriptive statistic (percentage and Frequencies) and inferential (person s correlation coefficient, independent sample t-test, and paired t-test). Results: The results shows that there is a high significant relationship between the pulmonary functions pre and post cardiac catheterization, and most the patients with low PFTs post angioplasty. Conclusions: The present study recommended the nurses whose work at the open Heart Center should teach the patient undergoing cardiac catheterization breathing exercises to increase the lung capacity as particular and the respiratory system as general and the patient should be given oxygen for at least 60 minutes before and after cardiac catheterization to ensure an increase in the oxygen level and perfusion in the body tissues.